Rheumatoid Arthritis and some Demographical and Clinical Parameters - tamara alkaaby; Raya Ezat Maroof; Ali Hussein AL-Hafidh (Al-SalamJournal for Medical Science, 2022)
Rheumatoid Arthritis is a heterogeneous, symmetrical chronic autoimmune inflammation of body joints, it infects the population with a ratio reaching 1% of the population's world, and it can lead to bone erosion and deformities, and finally damage. Smoking is one of the important factors that increase the risk of RA infections by aiding in citrullinated protein production, CRP increases in RA patients and binds with the severity of the disease. The aim of the study is to evaluate the CRP and smoking effects on RA patients. 150 blood samples were taken; 100 for RA patients and 50 for healthy control, the patients were taken from the Baghdad Teaching Hospital / Rheumatologically Consulting Clinic in the period from November 2021 to February 2022. The ages of patients range from 22 to 72 years old, and 26 to 62 years old was the age range of the healthy controls. 2ml of venous blood was taken in a gel tube for the CRP test by agglutination method. The result of the current study shows a highly significant differences between the RA patients and control groups in family history and CRP. While, it shows a non-significant difference for smoking.